Effects of mechanical forces and stretch on intercellular gap junction coupling - Salameh, Aida; Dhein, Stefan (Biochimica et biophysica acta, 2013)
Mechanical forces provide fundamental physiological stimulus in living organisms. Recent investigations demonstrated how various types of mechanical load, like strain, pressure, shear stress, or cyclic stretch can affect cell biology and gap junction intercellular communication (GJIC). Depending on the cell type, the type of mechanical load and on strength and duration of application, these forces can induce hypertrophic processes and modulate the expression and function of certain connexins such as Cx43, while others such as Cx37 or Cx40 are reported to be less mechanosensitive. In particular, not only expression but also subcellular localization of Cx43 is altered in cardiomyocytes submitted to cyclic mechanical stretch resulting in the typical elongated cell shape with an accentuation of Cx43 at the cell poles. In the heart both cardiomyocytes and fibroblasts can alter their GJIC in response to mechanical load. In the vasculature both endothelial cells and smooth muscle cells are subject to strain and cyclic stretch resulting from the pulsatile flow. In addition, vascular endothelial cells are mainly affected by shear stress resulting from the blood flow parallel to their surface. These mechanical forces lead to a regulation of GJIC in vascular tissue. In bones, osteocytes and osteoblasts are coupled via gap junctions, which also react to mechanical forces. Since gap junctions are involved in regulation of cell growth and differentiation, the mechanosensitivity of the regulation of these channels might open new perspectives to explain how cells can respond to mechanical load, and how stretch induces self-organization of a cell layer which might have implications for embryology and the development of organs. This article is part of a Special Issue entitled: The Communicating junctions, roles and dysfunctions. ► Cells can be affected by pressure, cyclic and static stretch, strain, shear stress. ► In this review, we describe how these various mechanical forces can be sensed by cells. ► We review how these mechanical forces lead to changes in the intercellular communication. ► This process leads to re-arrangement of cells and to changes in the cell's functional orientation. ► These processes are important for general understanding of cell biology and organ development.